Effective and fair cognitive terminal assignment scheme for cooperative spectrum sensing - WU Zhiqiang; LIU Qianli; LIU Jiabin; FENG Qing; XIAO Shanpeng; LIU Shang (Dianxin kexue)
Cooperative spectrum sensing is regarded as the foundation and a key stage of cognitive radio networks. The node allocation strategy during the spectrum detection process was directly determined by the results of joint spectrum sensing. Various methods for allocating cognitive terminals to enhance the efficiency and fairness of spectrum sensing were introduced. Aiming at the perceptual efficiency of different sub-bands, an indicator called the inefficient transmission parameter (ITP) was proposed to evaluate communication performance, and a closed-form expression solution to the perceptual efficiency optimization problem was provided. The designed scenarios included terminal pairs with the same frequencies having different perceptual properties and the same perceptual properties. For the perceived fairness among different sub-bands, two allocation algorithms were proposed: the arcuate allocation algorithm and the class division allocation algorithm. Fairness between sub-bands was measured by evaluating the worst perceived performance in the sub-band. In order to be applicable to actual scenarios, the frequency band property parameter was added to enhance fairness. This parameter was taken into account the priority and anti-interference ability of the main user using different frequency bands. Simulation results show that the proposed strategy significantly improves ITP in cognitive radio networks, especially when sub-band utilization is different, and the proposed arcuate allocation algorithm significantly improves the perceived fairness of the system.